GEOGRAPHIC INFORMATION SYSTEM IN REGIONAL ASSET MANAGEMENT AT BPKAD OF PALEMBANG CITY - Leni Novianti; Indra Griha Tofik Isa; Indri Ariyanti; Rika Sadariawati (IJISCS (International Journal of Information System and Computer Science), 2022)
Background: BPKAD Palembang City as a government agency for managing regional assets, which data on land and building asset management is still in the form of tabular documents. The process of visualizing land and building asset data can be represented through a Geographic Information System (GIS) for easy information and realizing transparent and serving government governance. Problem Formulation: (1) How is the implementation of web-based GIS in the management of regional assets in Palembang City, and (2) How is the level of effectiveness of web-based GIS in regional asset management in BPKAD Palembang City. Research objectives: (1) Provide information, monitoring and supervision to the government, especially BPKAD Palembang City on the classification and mapping of regional assets, and (2) Measure the level of effectiveness of GIS implementation in the management of regional assets. Research stages: Planning, Analysis, Design, Implementation, Testing and Integration, Survey. The final result is a Geographic Information System product that provides easy information, monitoring, and supervision for the Palembang City BPKAD with an effectiveness rate of 81%